Implementation of Paal Dua Terminal Node in Manado City, North Sulawesi Province - Umboh, Joop Z. C.; Kairupan, Sisca B.; Bulo, Laurens (Technium Social Sciences Journal, 2025)
The purpose of the research is to find out, analyze and describe how the Implementation of Paal Dua Terminal Node of Manado City. The method used in this research is qualitative research method. The results of the research are There are no special facilities for pregnant women, disabilities, the importance of Paal 2 Terminal as a vital object in the transportation system, with various aspects that affect comfort, security, supervision, and terminal management. Success in supervision explains the importance of cleanliness as part of terminal management to create a comfortable, safe, and decent environment for users. The importance of supervision of basic facilities and services at the terminal, which aims to maintain the comfort and satisfaction of users of transportation services. Challenges and efforts to manage security and handle emergency situations at the terminal, as well as the importance of coordination and adequate supporting facilities. Major constraints in the maintenance of terminal facilities, which have a direct impact on the comfort and satisfaction of service users. Parking area management is one of the main operational constraints at Paal 2 Terminal as it is a major source of congestion around the terminal. Lack of disability-friendly facilities as one of the main constraints at the terminal. The limited number of security personnel as the main obstacle in maintaining security at Paal 2 Terminal. As well as the lack of security technology at Paal 2 Terminal, which is an obstacle in creating a safe environment for terminal users. Behavioral constraints of terminal users, lack of security at night, and challenges in monitoring luggage at Paal 2 Terminal. The limited operating budget is a major challenge at Paal 2 Terminal, especially in increasing the number and quality of officers. Budget availability for facility maintenance is an important indicator in ensuring efficient terminal operations and user convenience. Utilization of terminal revenue sources as an indicator of success in budget management.